Singing madness: three performative analyses of the "mad scene" from Lucia di Lammermoor - Le Kay, Jo-Nette (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
This study describes three internationally recognised sopranos and their presentations of character psychology on stage, during their performances of the famous "mad scene" from Gaetano Donizetti's opera Lucia di Lammermoor. These sopranos are Joan Sutherland, Mariella Devia, and Lisette Oropesa. I use Margaret Kartomi's (2014) model of performativity to interpret the "madness" depicted by the three selected sopranos, as based on my interpretations of commercially released audio-visual recordings of their performances in the role of Lucia. Through analysing these performances with the help of Kartomi's performativity model (which focuses on persona, emotion-and intersubjectivity, and reception), my research determines "“ with speculative interpretation, and within the reasonable limits of standard psychiatric frameworks "“ which mental illnesses the sopranos can be understood to have portrayed in their interpretations of the role of Lucia. The study's goal is not to make an accurate mental health diagnosis of someone's portrayal of a fictional character. (Considering the fact that one cannot make accurate mental health diagnoses for people who do not exist.) Rather, my focus is to discover which dramatic and possibly musical characteristics are utilised to perform this fictional character and give expressive content to her "madness" . The concept of "madness" and its psychological characterisation during performance thus becomes the framework from which to interpret and understand vocal and acting techniques related to opera in general and to bel canto more specifically. My research findings are that the three performers use facial expressions, different aspects of using the voice through bel canto singing, and body movements as a way of expression. Bel canto characteristics include coloratura embellishments, fioritura, melismas, messa di voce, squillo and chiaroscuro. The sopranos also show musical and dramatic elements in how they respond to the flute or glass harmonica during the 'Mad Scene' "“ which counts as the personae expressed by the performers. These personae are further applied in the emotional and intersubjectivity and the reception aspects of Kartomi's performativity model. In the emotional and intersubjectivity aspect, the chorus and other characters singing on stage are read as emphasising the reaction of society on the mentally dysfunctional behaviour enacted by the sopranos. In the reception aspect, reviewers are used to filling in for audience members. I read their reactions as contributing factors in forming an understanding of the interpretations of the "mad scene" performed by the three sopranos. My reading of the three interpretations of the "mad scene" goes further by subjectively interpreting how these sopranos approximate different states of mental collapse. These readings include approximations of psychosis such as mania, dissociative personality disorder, and paranoid schizophrenic behaviour. Always, though, these mental health behaviours are identified as approximations to better understand vocal and acting techniques.
Keywords: Mental illness in music; Bel canto; Donizetti, Gaetano, 1797-1848 -- Lucia di Lammermoor -- Dolce suono; Coloratura soprano; Embellishment (Vocal music); Performativity